The role of the natural environment in disaster recovery: "We live here because we love the bush". (May 2019) - Block, Karen; Molyneaux, Robyn; Gibbs, Lisa; Alkemade, Nathan; Baker, Elyse; MacDougall, Colin; Ireton, Greg; Forbes, David
Abstract: This mixed-methods study explored the role of connection to the natural environment in recovery from the 'Black Saturday' bushfires that blazed across Victoria, Australia, in February 2009. Qualitative findings demonstrated that many participants had a strong connection to the natural environment, experienced considerable grief as a result of its devastation in the fires and drew solace from seeing it regenerate over the following months and years. Quantitative analyses indicated that a strong attachment to the environment was associated with reduced psychological distress, fewer symptoms of major depression and fire-related PTSD, and higher levels of resilience, post-traumatic growth and life satisfaction. While social connections are increasingly recognized as supportive of disaster recovery, the influence of landscapes also needs to be recognized in terms of the impact of their destruction as well as their therapeutic potential. Highlights: Residents in bushfire-affected regions described grief over environmental damage. Residents drew solace from regeneration of nature in the years that followed. Strong attachment to nature was associated with better mental health and wellbeing. Landscapes in this context are more than sites for social connection. Disaster recovery is impacted by their devastation and their therapeutic potential.